Sound pressure level in a lecture hall during occupied conditions / Muhammad Faris Ashman Isahak and Dr. Kwong Qi Jie - Isahak, Muhammad Faris Ashman; Kwong, Qi Jie (College of Built Environment, 2023)
Good acoustic levels in lecture halls can improve students' learning performance.